Removal Of Textile Dye By Electrochemical Treatment - Gun, Yin Farn (Universiti Sains Malaysia, 2006)
One of the main problems associated with wastewater from textile industries is colour. Reactive dyes in industrial discharge, in particular, are difficult to manage as they are not readily amenable to biological treatment. The present study employs an electrochemical method using cast iron electrodes and sodium chloride (NaCl) as electrolyte to decolourise synthetic wastewater containing reactive Red dye (Cibacron Red CR). The main objective of this study was to determine the optimum combination of influencing factor levels for dye removal. A laboratory-scale batch experiment was used to investigate the effect of operating parameters, electrolyte (NaCl) concentration (0.6-1.0 g/l), initial dye concentration (20-100 mg/l), current density (1-3 mA/cm2 ) and reaction time (20-60 min), on colour removal using cast iron electrodes. A scanning UV-visible spectrophotometer set at 525 nm was used to measure the absorbance before and after the dye solution was treated. NaCl concentration did not effect dye removal because its concentration used in this study was found to be greater than the optimum required. Removal was found to be highly dependent on, current density, initial dye concentration and reaction time. Increasing the current density and reaction time and lowering the initial dye concentration showed an increase in the colour removal. The experiment was conducted following a factorial design with 4 factors at 3 levels each. The results show that over 99% dye removal may be achieved under optimum operating conditions. The multiple correlation coefficient of determination, R-Squared was 0.8148. This shows that the actual data give a quite good fit to the predicted data.